2021
DOI: 10.29337/ijsp.156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Botulinum Toxin Type A Injections on Stricture Formation, Leakage Rates, Esophageal Elongation, and Anastomotic Healing Following Primary Anastomosis in a Long- and Short-Gap Esophageal Atresia Model – A Protocol for a Randomized, Controlled, Blinded Trial in Pigs

Abstract: Background: Esophageal atresia (EA) is a congenital malformation affecting 1:3000-4500 newborns. Approximately 15% have a long-gap EA (LGEA), in which case a primary anastomosis is often impossible to achieve. To create continuity of the esophagus patients instead have to undergo lengthening procedures or organ interpositions; methods associated with high morbidity and poor functional outcomes. Esophageal injections of Botulinum Toxin Type A (BTX-A) could enable primary anastomosis and mitigate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The authors found that the effect of statins and BoNT injections in preventing the development of strictures were comparable with each other, and the stricture occurrence rates in the statins and BoNT group were significantly lower than both the steroid treatment and the non-intervention approach (Table 3). The positive results of the abovementioned studies in humans are supported by several animal studies that show injection of BoNTs close to the site of esophagectomy can reduce the development of esophageal strictures [50,51].…”
Section: Esophageal Stricture (Es)mentioning
confidence: 74%
See 1 more Smart Citation
“…The authors found that the effect of statins and BoNT injections in preventing the development of strictures were comparable with each other, and the stricture occurrence rates in the statins and BoNT group were significantly lower than both the steroid treatment and the non-intervention approach (Table 3). The positive results of the abovementioned studies in humans are supported by several animal studies that show injection of BoNTs close to the site of esophagectomy can reduce the development of esophageal strictures [50,51].…”
Section: Esophageal Stricture (Es)mentioning
confidence: 74%
“…The positive results of the abovementioned studies in humans are supported by several animal studies that show injection of BoNTs close to the site of esophagectomy can reduce the development of esophageal strictures [ 50 , 51 ].…”
Section: Esophageal Stricture (Es)mentioning
confidence: 86%
“…A planned randomized controlled trial (RCT) study will include a 7-day waiting period from endoscopic BTX-A injections to surgery where a resection of a 3-cm segment of the esophagus will be performed, followed by an esophageal anastomosis, and a 14-day follow-up. 13…”
Section: Discussionmentioning
confidence: 99%